Risk of Acute Kidney Injury and Long-Term Outcome in Patients With Acetaminophen Intoxication: A Nationwide Population-Based Retrospective Cohort Study. Issue 46 (November 2015) - Chen, Yu-Guang; Lin, Cheng-Li; Dai, Ming-Shen; Chang, Ping-Ying; Chen, Jia-Hong; Huang, Tzu-Chuan; Wu, Yi-Ying; Kao, Chia-Hung
Abstract : Abstract: Acetaminophen (APAP) intoxication is a common cause of hepatic toxicity and life-threatening hepatic failure. However, few studies have investigated the possible association between APAP intoxication and acute kidney injury (AKI). We constructed a retrospective cohort study to clarify the relationship between APAP intoxication and the risk of AKI. We identified patients with APAP intoxication and selected a comparison cohort that was 1:4 frequency matched according to age, sex, and year of APAP intoxication diagnosis from the Taiwan National Health Insurance Research Database from 1998 to 2010. We analyzed the risks of AKI for patients with APAP intoxication by using Cox proportional hazards regression models. In this study, 2914 patients with APAP intoxication and 11, 656 controls were included. The overall risks of developing AKI were 2.41-fold in the patients with APAP intoxication compared with the comparison cohort. After we excluded APAP intoxication patients with coexisting AKI and hepatic failure/hepatitis, the overall risks of developing AKI were still 2.22-fold in the patients with APAP intoxication. There were 2 patients who had end-stage renal disease (ESRD) following APAP intoxication-related AKI. Limitations include retrospective review, selection bias, and absence of data on detail medications used, laboratory investigations and dosage of APAP intoxication. Our long-term cohort study results showed that AKI is a possible adverse effect among patients with APAP intoxication, regardless of whether patients have presented with hepatic toxicity. However, additional studies are necessary to clarify whether such patients can progress to ESRD.